Students Perspectives on Thesis Writing in English Academic Culture - Novita, Dewi (Jurnal Visi Ilmu Pendidikan, 2010)
Thesis writing is important in higher education because it shows the students ability in doing research and producing written academic results. Generally, it is assume that university students are educated people and therefore have an ability to produce a thesis. Yet, this is not always as easy as it seems. For students studying in English academic culture, for example, thesis writing brings two challenges, First, a challenge of writing in a language that is not their own, English. Second, a challenge of producing written work in a new cultural context, that is English academic culture. These challenges often cause great difficulties in producing the thesis for the Indonesian students. Key Word: Perspectives, Indonesian Students, Thesis, English Academic Culture.